2019
DOI: 10.1111/jfd.12962
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional characterization of Histone‐like DNA‐binding protein in Nocardia seriolae (NsHLP) involved in cell apoptosis

Abstract: Nocardia seriolae, a facultative intracellular bacterium, is the main pathogen of fish nocardiosis. Bioinformatic analysis showed that the histone‐like DNA‐binding protein (HLP) gene of N. seriolae (nshlp) encoded a secreted protein and might target the mitochondria in the host cell. To further study the preliminary function of HLP in N. seriolae (NsHLP), the gene cloning, extracellular products identification, subcellular localization, overexpression and apoptosis detection assay were carried out in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…This phenomenon also occurred on cultured eel, A. japonica (Kim et al., 2018). N. seriolae causes illness in fish and possesses several intracellular virulence factors (tyrosine phosphatase A, protein tyrosine phosphatase B, antigen 85 (Ag85), and TlyA protein) and produces an extracellular product (histone‐like DNA‐binding protein), which can cause immune depression, haemolysis and can induce disease in fish (Wang et al., 2019; Yasuike et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon also occurred on cultured eel, A. japonica (Kim et al., 2018). N. seriolae causes illness in fish and possesses several intracellular virulence factors (tyrosine phosphatase A, protein tyrosine phosphatase B, antigen 85 (Ag85), and TlyA protein) and produces an extracellular product (histone‐like DNA‐binding protein), which can cause immune depression, haemolysis and can induce disease in fish (Wang et al., 2019; Yasuike et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…piscicida (Costa‐Ramos et al., 2011), and AIP56‐induced phagocyte apoptosis involves activation of caspase‐3 and mitochondria as shown by loss of ΔΨm. Previous study had reported that histone‐like DNA‐binding protein from N. seriolae was considered to be a virulence factor that induces cell apoptosis by degradation of mitochondrial membrane potential, activation of caspase‐3 and pro‐apoptosis genes (Wang et al., 2019). Based on the previous studies and the results obtained in this study, it is a reason to believe that GluNS is the potential virulence factor of N. seriolae .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, N. seriolae has become the main pathogen of fish nocardiosis recently. The outbreak of fish nocardiosis induced by N. seriolae caused heavy economic losses in aquaculture(Chen et al., 2019; Wang et al., 2019). Moreover, the pathogenic virulence factors of N. seriolae are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Nocardia seriolae is a Gram‐positive facultatively intracellular pathogen, which belongs to actinomycetes, Nocardia family and Nocardia genus in taxonomy, and can infect the fish with low immunity through gills or wound (Nayak, Shibasaki and Nakanishi, 2014; Wang et al, 2019). Notably, N. seriolae can evade intracellular killing after being engulfed by macrophages and disseminate in the host and cause widespread infection along with the migration of macrophages (Barry & Beaman, 2007; Ho et al, 2016).…”
Section: Introductionmentioning
confidence: 99%